2018
DOI: 10.1007/s11044-018-09636-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the tyre–road interaction with a non-smooth delayed contact model

Abstract: In this study a tyre model is developed for multibody dynamics software. Vibrations of a towed wheel excited by the lateral deformation of the tyre are analysed with the help of numerical simulations. In our calculations the time delay in the tyre-ground contact as well as the partial side slip are considered making it possible to capture the dynamic deformation of the contact patch centre-line with relatively low number of parameters and computation time. As a result the hysteresis effect in the stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Nevertheless, neither model can provide bistable parameter domains in the one degree of freedom model of towed wheels, which were otherwise experimentally presented in [5,24,39]. Additional dry friction at the king pin can be one explanation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, neither model can provide bistable parameter domains in the one degree of freedom model of towed wheels, which were otherwise experimentally presented in [5,24,39]. Additional dry friction at the king pin can be one explanation [24].…”
Section: Introductionmentioning
confidence: 99%
“…As several former studies showed, these oscillations have very rich dynamics and the associated vibrations are essentially nonlinear [17,18]. In experiments, socalled bistable parameters were identified [1] where although the rectilinear motion is stable, it has a finite domain of attraction. This means that depending on the initial conditions, the system can converge either to the straight-line motion or to a large-amplitude periodic solution (shimmy) at the same towing speed.…”
Section: Introductionmentioning
confidence: 91%
“…This error could be adjusted via the stretched string tyre model [12]. As shown in [1], this model provides qualitatively similar, but quantitatively better results for the critical towing speed. However, by means of the stretched string model, sliding can be considered only with differential equations instead of pre-defined sliding limits.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the fundamental phenomena of towed wheels is the self-excited oscillations called shimmy, which has been intensively studied in the literature (see [18,21] and their references). There are many possibilities for modelling the tyre and the vehicle, and the resulting models often lead to complex mathematical models including, for example, time delay [3,4].…”
Section: Introductionmentioning
confidence: 99%